147 Effect of Within-pen Variation in Weaning Weight on the Growth Performance of Nursery Pigs. (7th May 2021) - Morris, Jenny R; Ellis, Michael; Shull, Caleb M
Abstract: This study evaluated the effect of housing newly-weaned pigs in uniform versus mixed weight groups on nursery growth performance (5.9 ± 1.1 to 26.2 ± 2.9 kg BW). Pigs were assigned to a weaning weight (WW) quartile: Q1 (light; 4.2 ± 0.1 kg), Q2 (medium-light; 5.5 ± 0.1 kg), Q3 (medium-heavy; 6.3 ± 0.2 kg), and Q4 (heavy; 7.5 ± 0.1 kg). A RCBD was used (blocking factor = start date) with 5 treatments: Control (equal number of pigs from each quartile); Uniform Q1 (all pigs from Q1); Uniform Q2 (all pigs from Q2); Uniform Q3 (all pigs from Q3); Uniform Q4 (all pigs from Q4). There were 16 replicates and 3, 503 pigs, with mixed-gender pens of 44. Pen was the experimental unit; data were analyzed using PROC MIXED of SAS (fixed effect = treatment; random effect = replicate). Overall ADG and ADFI increased (P < 0.05) according to WW quartile for the Uniform treatments, with the Control being intermediate. There were no differences (P > 0.05) between treatments for Overall G:F. A contrast statement was used to compare Control to the mean of all 4 Uniform treatments. Compared to Control, the mean of the 4 Uniform treatments had similar (P > 0.05) overall ADG (0.44 vs. 0.44 kg, respectively) and ADFI (0.72 vs. 0.68 kg, respectively), but greater (P < 0.05) overall G:F (0.637 vs. 0.611, respectively). Comparison of pigs from each quartile within Control pens with the respective quartile in Uniform pens suggested no effect (P > 0.05) of weight quartile on ADG (respective means for Control vs Uniform: Q1 0.34 vs. 0.36 kg; Q2 0.39 vs. 0.40 kg; Q3 0.42 vs. 0.42 kg; Q4 0.47 vs. 0.45 kg). These results suggest that penning nursery pigs in uniform versus mixed weight groups had limited effect on growth performance.